Validation of the Cardiff acne disability index and the impact of educational materials in a Romanian cultural adaptation context. (31st January 2023) - Cretu, Stefana; Dascalu, Mihai; Salavastru, Carmen‐Maria
Abstract: Background: Acne has a high impact on patients being a chronic, common, and visible skin condition. Knowledge regarding treatment improves outcomes. The Cardiff Acne Disability Index (CADI) is commonly used in clinical practice for quality‐of‐life assessment. It has been validated in many languages, however, not in Romanian. Aims: To validate the Romanian adaptation of the CADI and educational materials for acne patients. Patients and Method: A 12‐week prospective cross‐sectional Web‐based study, including 3rd‐ to 5th‐year medical students attending our university was conducted. We obtained permission from the CADI copyright owner and performed the steps of the standardized translation process. The Romanian CADI adaptation was delivered online in a test–retest setup, during which participants were offered acne educational materials and completed a knowledge evaluation questionnaire. Results: A total of 95 complete answers were analyzed. The Romanian CADI adaptation showed good internal consistency, with Cronbach's α  = 0.807 in the first application and Cronbach's α  = 0.839 in the second. High test–retest reliability was observed, with interclass correlation coefficient ICC = 0.987 and Spearman's rank correlation coefficient r s  = 0.970 for the overall CADI scores between the two administrations. The mean baseline score in the knowledge evaluation questionnaire was 15.52 points (±1.556), with a statistically significant improvement after exposure to the educational material ( Z  = −7.207, p  < 0.001). This material was considered useful or very useful by 78(82.8%) participants. Conclusion: Romanian acne patients can benefit from CADI, a reliable and disease‐specific tool for quality‐of‐life evaluation, together with validated, guideline‐aligned educational material in their language.